Features of Long Waves in the Area of Cape Svobodny (South-Eastern Part of Sakhalin Island, Russia) During the Passage of Cyclones - Kurkin Andrey; Kovalev Dmitry; Kurkina Oxana; Kovalev Petr (Russian Journal of Earth Sciences, 2023)
The study of marine wave processes was carried out according to field observations using two autonomous wave recorders, temperature and weather station installed near Cape Svobodny, south-east coast of Sakhalin (Russia). Spectral and cross-spectral analysis showed the existence of edge waves with a period of about 10.7 min. Measurements in 2021 showed that the edge wave existing from Cape Ostry to Cape Svobodny, just beyond the cape Svobodny significantly weakens and does not spread further. The analysis of temperature fluctuations for the period range 1–80 hours showed that since the periods of spectral density peaks of water temperature fluctuations for periods longer than 5 hours do not coincide with the periods of peaks of sea level fluctuations, these peaks are determined by internal waves. Temperature fluctuations with a period of 25.5 hours detected by peaks in the spectra can be excited by shelf waves with the same period because of their interaction with islands, coastal currents and baroclinic instability. The analysis of cyclone wakes based on the time course of temperature fluctuations made it possible to establish that cyclone wakes are formed when the water temperature of the upper mixed layer exceeds 10 ◦C, and internal waves with a period of about 13 hours are also present when cyclones do not move near the point of installation of devices and the water temperature is below 10 ◦C. The Burger number is determined, which makes it possible to correct the range of existence near inertial internal waves and determine this range periods of 12.1–18.2 hours. Using the results of a simple linear Phillips model, the possibility of baroclinic instability for periods of shelf waves is estimated. It is shown that baroclinic instability is possible for waves with a period of 13.1 hours, and even more so for shelf waves with a significantly longer wavelength.